Comparing the efficacy between ferrous carboxymaltose and iron sucrose therapy in iron deficiency anemia during pregnancy in Obstetrics and Gynecology ward at tertiary care hospital, Jaipur - Kamal Saini; Divyani Agrawal; Rajveer Singh; Shambaditya Goswami (Al Ameen Journal of Medical Sciences, 2020)
Aim: Comparing the efficacy between ferrous carboxymaltose and iron sucrose therapy in iron deficiency anemia during pregnancy in obstetrics and gynecology ward at tertiary care hospital, Jaipur. Methods: The study was conducted on 60 pregnant women who were diagnosed with iron deficiency anemia in the department of obstetrics and gynecology at NIMS hospital, Jaipur. The subjects were divided into two groups, first group was treated with iron sucrose (200mg/ dose) and second group was treated with ferrous carboxymaltose (500mg/ dose). Results: The mean rise of hemoglobin was 2.92 g/l for Ferrous Carboxymaltose and 1.08 g/l for iron sucrose. The rise in the hemoglobin concentration shows that ferrous carboxymaltose is more efficaous than iron sucrose. Conclusion: In this study it was found that ferrous carboxymaltose is efficaous in comparison to the Iron sucrose among the pregnant women with Iron deficiency anemia.